The mysterious case of strength within triathlon - Smith, D. (Science + Triathlon 2015 World Conference, 2015)
I just wonder how much training can be done and done well in a week. Our sport is always a compromise with too much to do, and not enough training time and energy to get it done. Extra work must have a purpose and some real return for the time and energy investment.